Oleic acid activates TGFβ-Smad3 signaling to promote ovarian cancer progression - Zhengyang Guo; Yinjia Li; Yunyun Guo; Aosong Zhang; Xiao Huo; Ying Song; Bing Li; Yuanjun Tang; Tianhui He; Tong Liu; Lixiang Xue; Yi Qu; et al. (Journal of Ovarian Research)
Abstract Background Ovarian cancer represents the most aggressive and lethal gynecological cancer, frequently demonstrating a distinct propensity for abdominal metastasis. Malignant ascites caused by abdominal metastasis provide a tumor microenvironment (TME) in ovarian cancer. Notably, oleic acid is abundant in ovarian cancer ascites, though its functional significance in TME modulation and tumor metastatic regulation remains poorly characterized. Stearoyl-CoA desaturase 1 (SCD1) is the key enzyme in the synthesis of oleic acid. Our study systematically explores the pathological role of oleic acid and evaluates the therapeutic effects of SCD1 inhibitor in ovarian cancer progression. Results Oleic acid treatment significantly enhanced proliferation of ovarian cancer cells and patient-derived organoids. Remarkably, oleic acid also increased membrane fluidity and promoted cell migration. Mechanistically, TGFβ-Smad3 signaling cascade is selectively activated by oleic acid, and inhibited by SCD1 suppression. Importantly, activation of Smad3 caused by oleic acid treatment triggered epithelial-mesenchymal transition of ovarian cancer cells. Clinical relevance was established that SCD1 expression was positively correlated with the activity of Smad3 in ovarian cancer tissues. Finally, in vivo studies showed that SCD1 inhibitor treatment suppressed tumor progression during intraperitoneal dissemination. Conclusion This study provides novel insights into the supporting role of oleic acid in fueling tumor proliferation and metastasis, mechanistically associated with its specific activation of TGFβ-Smad3 signaling. Therapeutically, pharmacological targeting oleic acid synthesis by SCD1 inhibitor emerges as a promising strategy for precision oncology in ovarian cancer management.